KELAYAKAN PENDIRIAN USAHA ANGKUTAN UDARA NIAGA TIDAK BERJADWAL - Fajar Hidayat; Francis Tantri; Devi Marlita (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2016)
The aims of this  study is  to determine feasibility study of commercial air charter in PT. Sukses Mandiri Aviation. This research was conducted at PT. Sukses Mandiri Aviation, by using a qualitative descriptive research method to analyze marketing aspects of the market and financial feasibility studies. The result shows that PT. Sukses Mandiri Aviation has a captive market by cooperating with charter aircraft. Results of analysis of financial projections on the financial aspects of the feasibility study are: NPV is positive, the profitability is more than 1 (one), the IRR is greater than the interest, the payback period is less than the life of the investment,and financial ratios have met the requirements of the rules and regulations.